Analisis Alokasi Joint Cost dalam Menentukan Harga Pokok Produksi di Adilah Garden - Nur Fadillah; Nurfarizha Fazhirawati; Nina Yustina Yasmin; Rahayu Indrisari; Andi Chairil Furqan (STIE KASIH BANGSA, 2025)
This study discusses the allocation of joint costs in determining the cost of production at Adilah Garden. Joint costs are costs incurred from processing raw materials until the product can be separated. The purpose of this study is to calculate the cost of production using the relative selling value method and compare it with the calculations made by Adilah Garden. The methods used are unstructured interviews and documentation, with source triangulation for data validation. The results show that the calculation of the cost of production through the allocation of joint costs is lower than the method used by Adilah Garden, which indicates the need for improvements in the company's cost accounting system.